PENERAPAN MODEL PEMBELAJARAN ACCELERATED LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS PESERTA DIDIK PADA MATERI ZAT DAN WUJUDNYA - Asri Muslimah Syamsi; Chaerul Rochman; Heni Rusnayati (UIN Sunan Gunung Djati Bandung, 2016)
The purpose of study is to determine the feasibility of learning processes and increase science literacy skills of learners using 'Accelerated Learning' model of learning on the material substance and its form. The method used in this research is pre-experiment. The study was conducted in Triyasa junior high school Bandung class VII-B. The sample in the study were 48 students who were selected using random sampling techniques. Data keterlaksanaan activity of teacher and students is obtained through observation sheets, while data on the literacy skills of learners is obtained through the test description. The results obtained in this study: (1) feasibility study by using 'Accelerated Learning' 'model of learning' is in very good category; (2) the literacy skills of learners sins increase in gain results. The magnitude of the increase scientific literacy of students can be seen from the average N-Gain learners of 0.56 categorized being. Thus there is increasing scientific literacy capability of learners through the 'Accelerated Learning' model of learning in material substance and its form.